National protectionism and common trade policy - Georg Koopmann (Intereconomics, 1984)
The EC recently created a new instrument of trade policy to deter illicit trade practices. A major part of its purpose is to strengthen the Community's authority in the area of trade policy and counter the spread of international protectionism within the Community. The following article demonstrates, among other things, that protectionism in the Community cannot offer a workable alternative to this course.
Keywords: 330; EC